"Don't lose hope early": Hemorrhagic diffuse axonal injury on head computed tomography is not associated with poor outcome in moderate to severe traumatic brain injury patients. Issue 3 (March 2018) - Henninger, Nils; Compton, Rebecca A.; Khan, Muhammad W.; Carandang, Raphael; Hall, Wiley; Muehlschlegel, Susanne
Abstract : BACKGROUND: Diffuse axonal injury (DAI) on magnetic resonance imaging has been associated with poor functional outcome after moderate-severe traumatic brain injury (msTBI). Yet, DAI assessment with highly sensitive magnetic resonance imaging techniques is unfeasible in the acute trauma setting, and computed tomography (CT) remains the key diagnostic modality despite its lower sensitivity. We sought to determine whether CT-defined hemorrhagic DAI (hDAI) is associated with discharge and favorable 3- and 12-month functional outcome (Glasgow Coma Scale score ≥4) after msTBI. METHODS: We analyzed 361 msTBI patients from the single-center longitudinal Outcome Prognostication in Traumatic Brain Injury study collected over 6 years (November 2009 to November 2015) with prospective outcome assessments at 3 months and 12 months. Patients with microhemorrhages on CT were designated "CT-hDAI-positive" and those without as "CT-hDAI-negative." For secondary analyses "CT-hDAI-positive" was stratified into two phenotypes according to presence ("associated") versus absence ("predominant") of concomitant large acute traumatic lesions to determine whether presence versus absence of additional focal mass lesions portends a different prognosis. RESULTS: Seventy (19%) patients were CT-hDAI–positive (n = 36 predominant; n = 34 associated hDAI). In univariate analyses, CT-hDAI–positive status was associated with discharge survival ( p = 0.004) and favorable outcome at 3 months ( p = 0.003) and 12 months ( p = 0.005). After multivariable adjustment, CT-hDAI positivity was no longer associated with discharge survival and functional outcome (all p s > 0.05). Stratified by hDAI phenotype, predominant hDAI patients had worse trauma severity, longer intensive care unit stays, and more systemic medical complications. Predominant hDAI, but not associated hDAI, was an independent predictor of discharge survival (adjusted odds ratio, 24.7; 95% confidence interval [CI], 3.2–192.6; p = 0.002) and favorable 12-month outcome (adjusted odds ratio, 4.7; 95% CI, 1.5–15.2; p = 0.01). Sensitivity analyses using Cox regression confirmed this finding for 1-year survival (adjusted hazard ratio, 5.6; 95% CI, 1.3–23; p = 0.048). CONCLUSION: The CT-defined hDAI was not an independent predictor of unfavorable short- and long-term outcomes and should not be used for acute prognostication in msTBI patients. Predominant hDAI patients had good clinical outcomes when supported to intensive care unit discharge and beyond. LEVEL OF EVIDENCE: Prognostic study, level III. Abstract : Supplemental digital content is available in the text.